Efecto in vitro de la miel de Apis mellifera frente a Escherichia coli y Candida albicans - Adrianzén Ramírez, Jilwer Joel (2017)
This research work, was aimed to evaluate the in vitro effect of honey from Apis mellifera against Escherichia coli and Candida albicans, determining the physico-chemical characteristics, secondary metabolites and determine the minimum concentration inhibitory (MIC) and minimum bactericidal concentration (CMB) of honey from Apis mellifera against Escherichia coli and Candida albicans; coming from the province San Ignacio, Department of Cajamarca-Peru, all the physicochemical tests are within the standards set by the Codex Alimentarius and the National Honey Board. The values of the free acidity was 19.5 meq/kg of honey ± 1.31, moisture 19.4%, activity diastase 12 on the scale of Goethe ± 0.58, ash 0.824 g / 100g of honey ±0. 07 and reducing sugars 66.8g / 100g of honey ± 1.85; In addition the pH 4.18 ± 0.20, 1.44 g/mL ± 0.05, total solids density was 80.6%, index of refraction 1.4876 ± 0.58, Brix degrees of 79 ± 0.58, solid soluble 79, insoluble solids of 0. 058g / 100g ± 0.019 that also meet within the established range. In the definition of secondary metabolites, using color and precipitation reactions, flavonoids, anthocyanins, saponins, phenols and alkaloids were qualitatively identified. Finally was determined the antimicrobial effect in vitro using the technique of macrodilucion showing the minimum inhibitory concentration (MIC) of 50% and minimum bactericidal concentration (MBC) of 80% for Escherichia coli, and a 60% MIC and MBC of 90% for Candida albicans